PENYEDERHANAAN BIROKRASI TERHADAP KEBIJAKAN OTONOMI KHUSUS PROVINSI PAPUA : (Studi pada Bagian Organisasi Sekretariat Daerah Kabupaten Mimika) - Novaly Abby Tomasouw (Jurnal Administrasi Publik, 2022)
Simplification of the Bureaucracy is part of the implementation of bureaucratic reform to achieve the main goals of regional government that are effective and efficient related to institutions, human resources and procedural systems to create good governance. and office simplification. The authority and specificity of the Mimika district is because it is part of the special autonomous region in the Province of Papua, namely the Institution and Management of ASN. Institutions in the customary territory in Papua consist of 5 customary territories so that the Mimika Regency is the customary territory of Mee Pago due to ethnic similarities so it needs to be adapted to regional needs in the development of diverse human resources while for ASN management it is necessary to pay close attention to the Mimika Regency Government, ASN OAP is a priority primarily by being given opportunities for capacity building, leadership training, trainings that can broaden their horizons so that there is a change in mindset to develop and lead the region so that they can create innovations in accordance with ethnic similarities in Mimika Regency